(NfILOSOFIQ(B, (NFIZIKA(B, (NMIKROMIR (B/s - (NpAN^ENKO(B, (NaLEKSANDR iWANOWI^s; (NmOISEEW(B, (Nn(B.(Nn(B.s ((NmOSKWA (B:s (NnAUKA(B,s, 1988)
(NbIBLIOGR(B. (NW PRIME^(B.: (NS(B. 186-192s
(Nan sssrs
Keywords: (NfIZIKA (B- (NfILOSOFSKIE PROBLEMYs